2022
DOI: 10.7554/elife.70173
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic mechanisms in the gating of resurgent Na+ currents

Abstract: The resurgent component of the voltage-gated sodium current (INaR) is a depolarizing conductance, revealed on membrane hyperpolarizations following brief depolarizing voltage steps, which has been shown to contribute to regulating the firing properties of numerous neuronal cell types throughout the central and peripheral nervous systems. Although mediated by the same voltage-gated sodium (Nav) channels that underlie the transient and persistent Nav current components, the gating mechanisms that contribute to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 58 publications
(108 reference statements)
1
21
0
Order By: Relevance
“…Moreover, the subsequent addition of ranolazine, still during continued exposure to picaridin, was able to attenuate the I Na(R) magnitude, especially at the level of −50 mV. In accordance with previous reports showing that the I Na(R) magnitude may alter the I Na(T) inactivation during high-frequency stimulation [ 32 , 51 , 52 , 53 , 55 , 56 , 57 , 58 , 63 , 68 ], the current investigations allowed us to indicate that the existence of picaridin may perturb the electrical behaviors (e.g., aberrant and rapid firing of action potentials) residing in varying excitable cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the subsequent addition of ranolazine, still during continued exposure to picaridin, was able to attenuate the I Na(R) magnitude, especially at the level of −50 mV. In accordance with previous reports showing that the I Na(R) magnitude may alter the I Na(T) inactivation during high-frequency stimulation [ 32 , 51 , 52 , 53 , 55 , 56 , 57 , 58 , 63 , 68 ], the current investigations allowed us to indicate that the existence of picaridin may perturb the electrical behaviors (e.g., aberrant and rapid firing of action potentials) residing in varying excitable cells.…”
Section: Discussionsupporting
confidence: 91%
“…I Na(R) has been increasingly demonstrated to be responsible for burst generation and membrane excitability present in different excitable cells [ 32 , 41 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. In this regard, we, thus, next wanted to study if the existence of picaridin produced any effects on I Na(R) identified from these cells.…”
Section: Resultsmentioning
confidence: 99%
“…I NaR was first measured in cerebellar Purkinje neurons (Raman & Bean, 1997) and because I NaR is a depolarizing current activated by membrane repolarization, such as the downstroke of an action potential, this depolarizing Nav current is hypothesized to be associated with supporting high rates of repetitive firing. To test this role directly, we used a Markov kinetic state model (depicted in Figure 1B), which accurately reproduces the voltage and time dependent properties of Purkinje neuron Nav currents (Ransdell et al, 2022), to test directly how I NaR properties affect Purkinje neuron repetitive firing. Development of the Nav conductance model is published in Ransdell et al (2022) and is based on Nav current properties recorded from C57bl/6 mouse Purkinje neurons.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the b3s rate constant changed from 0.94767 to 3.76696 at −45 mV in the ‘I NaR increased’ model and in the ‘I NaR decreased’ model, the b2 rate constant changed from 0.1081 to 3.884 at −45 mV. In order to generate additional models, properties of the originally developed (nominal) model were modified by adjusting values in a parameter optimization algorithm scripted in MATLAB (MathWorks) and previously described in (Moreno et al, 2016; Ransdell et al, 2022). The rate constant values for the nominal and each manipulated model are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This makes it possible that FHF4 isoforms regulate Nav1.6 I NaR in neurons, at least in part, by reducing channel fast inactivation, instead of direct mediating I NaR . Computational modeling of I NaR generation in mouse cerebellar Purkinje neurons suggests that blocking particle-independent mechanisms may account for TTX-sensitive I NaR in some neuronal populations (Ransdell et al, 2022).…”
Section: Discussionmentioning
confidence: 99%